Studi Biblika Otoritas Penciptaan terhadap Era Rekayasa Gender - Nikarni Zai; Mozes Lawalata (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2025)
This article explores the authority of creation from a biblical perspective, focusing on the phenomenon of gender engineering as an ethical and theological challenge in the modern era. The study is grounded in the Christian belief that the human body is a creation of God, endowed with sacred value, divine dignity, and spiritual purpose. Employing an interdisciplinary approach, this research integrates insights from theology, medical science, and sociology. Its aim is to provide profound theological reflections on bodily modification in light of Christian values and to formulate an ethical framework to help Christians navigate these complex developments. The findings reveal that gender engineering creates a paradox between human freedom and divine authority. Extensive bodily modifications may be seen as violations of the sanctity of the body and the sovereignty of God. Within Christian thought, the human body is not merely a physical entity but a dwelling place of the Holy Spirit, thus requiring deep respect for its dignity. This study offers a significant contribution by presenting a biblically grounded ethical guide to help Christians understand and respond to the moral challenges posed by advances in modern medical technology.